(untitled) (Web of Teachers: Inderscience Research, 2025)
The article deals with the issues of scientific and methodological justification of information resources for the preparation of future teachers for professional activities based on digital technologies. This statue can be used by those who are aware of the problems of increasing the qualifications of future specialists.